Effectiveness of educational training program on the knowledge of COTPA Act among the nonteaching staff of a tertiary care hospital - Sourabh Paul; Bhola Nath; Aswani K. Seth; Neeraj Pawar; Tarun Chhabra (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Globally, tobacco is among the leading factors attributable to death. The nonteaching staff plays a pivotal role in making a campus a "tobacco-free zone." The objective of the study is to assess the effectiveness of an educational training program conducted on the Cigarette and Other Tobacco Products Act (COTPA) 2003 among nonteaching staff of a tertiary care hospital. METHODS AND MATERIALS: A hospital-based cross-sectional study was conducted among 500 nonteaching staff of a tertiary care hospital in the Raebareli district of Uttar Pradesh, India. An educational training program on COTPA 2003 was conducted in collaboration with the State Tobacco Control Cell. Data were collected before (pre-test) and after (post-test) the training program. A paired t-test was applied to compare both knowledge scores. Multiple linear regression analysis was conducted to identify the factors associated with knowledge scores. RESULTS: Around 187 (37.4%) security personnel, 198 (39.6%) housekeeping staff and 115 (23%) hospital attendants participated in the study. The pre-test mean (± standard deviation (SD)) knowledge score was 4.91 ± 1.59 whereas post-test mean (± SD) knowledge score was 7.91 ± 1.42. The pre-test knowledge score was associated with residence, age, and history of tobacco consumption of study participants. The female gender was associated with the pre-test knowledge score having a standardized coefficient -0.49 (P value = 0.009). The post-test knowledge score was associated with a history of tobacco consumption with a standardized coefficient of 0.42 (P value = 0.012). CONCLUSION: The educational training program improved the knowledge of the study participants with maximum improvement among the housekeeping staff. The history of tobacco consumption emerged as a significant factor affecting knowledge even after the training program.